2017
DOI: 10.1097/opx.0000000000001118
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Status in Nepalese Pre-Term and Full-Term Infants Early in Life

Abstract: Pre-term infants who do not develop ROP show a trend toward increasing myopia and demonstrate greater astigmatism and anisometropia than full-term infants in their first 6 months of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
5
5
1
Order By: Relevance
“…Therefore, infants exhibit rapid changes of the refractive states in the first few months of life after premature birth. Although it has been reported that there was a significant difference in astigmatism, and anisometropia between full-term and preterm infants without ROP by 6 months of age, 24 in our study, the astigmatism and anisometropia were not related at 40 months of age. The reason for this is thought to be that the refractive error and most ocular components displayed an early exponential phase of rapid development during the first 1-2 years of life.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, infants exhibit rapid changes of the refractive states in the first few months of life after premature birth. Although it has been reported that there was a significant difference in astigmatism, and anisometropia between full-term and preterm infants without ROP by 6 months of age, 24 in our study, the astigmatism and anisometropia were not related at 40 months of age. The reason for this is thought to be that the refractive error and most ocular components displayed an early exponential phase of rapid development during the first 1-2 years of life.…”
Section: Discussioncontrasting
confidence: 95%
“…Our results indicate that clinically stable pre-term infants may have altered emmetropization [27] since a higher number of preterm infants demonstrated myopic refractive errors than their full-term peers. This finding is consistent with previous studies that suggest children born preterm are at a higher risk of developing myopia [28][29][30]. With regard to the VEP parameters, pre-term infants had relatively prolonged and diminished VEPs than their full-term counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…After that, the mean dioptric value gradually and continuously declined by 6 months of PA. at 6 months of PA, the SE was + 2.00 ± 0.17D in NC group and + 2.08 ± 0.23D in IVF group. Uprety S [14] found the SE in the pre-term infants was + 0.84 ± 1.72D at birth, however, there was a shift toward myopia at 6 months of age (SE = -0.33 ± 1.95D), which was quite different from ours. Shu-Juan Yu [15] studied the evolution of the refractive status in a large sample size in China and found the refractive state reached the top (+ 2.43 ± 1.46 D) at the age of one to two months.…”
Section: Discussioncontrasting
confidence: 92%